Influence of different culture media on growth and sporulation of fungal pathogen isolated from pineapple rot disease / Siti Nor Atikah R.Azani - R.Azani, Siti Nor Atikah (Faculty of Plantation and Agrotechnology, 2018)
The one of main constrains of pineapple production in Malaysia is disease attack that could reduce the quality and quantity of fruit production. Many species of fungus are related with pineapple especially rot disease. Therefore, correct and fast identification is important so that we could develop proper control method. The identification was based on morphological characteristics of the fungi in which the reliability of the characteristics heavily depends on the type of media used. This is because, different media might showed different characteristics of fungus. The objective of the study is to determine the suitable growth media to identify different type of pathogen associated with pineapple rot disease. Three types of media were used in this study which are Potato Dextrose Agar (PDA), Tomato Juice Agar (TJA) and Cornmeal Agar (CMA). Based on the result, it shows that Fusarium growth better in TJA while Colletotrichum and Trichoderma are growth better in CMA. As a conclusion, the types of media used will influence the characteristics produce by the fungus.